Changes in the Structure and Digestibility of Myoglobin Treated With Sodium Chloride - Liu, Hui (Curr Dev Nutr, 2021)
OBJECTIVES: Changes in the structure of myoglobin affect its digestibility and myoglobin can't be completely broken down of pepsin. The exact mechanism of this breakdown is not clear. It can be inferred that myoglobin is broken down into polypeptides whose structures do not fully conform to the spatial characteristics of digestive enzymes. Myoglobin dissolution in different salt concentrations and changes in secondary structure were examined by spectroscopic examination. The molecular dynamics simulation was used to study the stability of these structural changes and their combination with digestive enzymes. Finally, since the products of digestion are determined by the catalytic centers of digestive enzymes, the substrate channel is extended to study the relationship between digestive enzymes and substrates. METHODS: In this study, different concentrations of sodium chloride were added for a certain period of time in advance to detect changes in the secondary structure of myoglobin, leading to changes in digestibility. Myoglobin and digestive enzymes were docked for molecular dynamics simulations to analyze the energy and structural changes in the interactions between substrates and proteins. RESULTS: Salt-treated protein can affect the secondary structure changes of protein. High concentration of salt-treated protein will lead to protein aggregation and denaturation, affecting digestibility. Low concentration of salt-treated protein may lead to exposure of sleeping areas, reducing digestibility. In terms of structure, salt ions lead to changes in the bonding of amino acids in the protein and affect the substrate's entry into the enzyme activity center. CONCLUSIONS: Treatment of myoglobin with different salt concentrations did not change its tertiary structure but low salt concentrations lowered its digestibility, probably due to salt ions altering a number of key amino acid bonds, making the structure more stable and less susceptible to digest. Some low molecular weight peptides remain after pepsin digestion. This may be due to the distance between the key amino acids in the active catalytic center of pepsin being insufficient to form stable conformations with small peptides. FUNDING SOURCES: This work was supported by the grants from NSFC (32072211).